2020
DOI: 10.1021/acssuschemeng.0c02749
|View full text |Cite
|
Sign up to set email alerts
|

Facile Green Synthesis of New Copper-Based Metal–Organic Frameworks: Experimental and Theoretical Study of the CO2 Fixation Reaction

Abstract: Two new entangled Cu(II)-based metal-organic frameworks (MOFs) have been synthesized, namely [Cu(BDC)(BPDB) 0.5 ] n (PNU-25) and [Cu(NH 2 -BDC)(BPDB) 0.5 ] n (PNU-25-NH 2 ), using a H 2 O-MeOH solvent mixture. Both the PNU-25 and PNU-25-NH 2 MOF materials were characterized by various analytical techniques and their catalytic potential of CO 2 fixation into cyclic carbonates at an atmospheric pressure, a low reaction temperature, and in the neat conditions were demonstrated. The amine-functionalized PNU-25-NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 62 publications
2
61
0
Order By: Relevance
“…Its high CO 2 adsorption capacity can be attributed to the strong dipole–quadrupole interaction between the CO 2 and N–H groups in the Gua ligand. 25,45 To further investigate their isosteric enthalpy ( Q st ) for CO 2 adsorption, the Clausius–Clapeyron equation was applied to their corresponding experimental isotherm at 273 and 298 K. The Q st value of UiO-66-Gua 0.2 ( s ) for CO 2 was found to be 29.0 kJ mol −1 , which is higher by ca . 5% than that of UiO-66( s ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its high CO 2 adsorption capacity can be attributed to the strong dipole–quadrupole interaction between the CO 2 and N–H groups in the Gua ligand. 25,45 To further investigate their isosteric enthalpy ( Q st ) for CO 2 adsorption, the Clausius–Clapeyron equation was applied to their corresponding experimental isotherm at 273 and 298 K. The Q st value of UiO-66-Gua 0.2 ( s ) for CO 2 was found to be 29.0 kJ mol −1 , which is higher by ca . 5% than that of UiO-66( s ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the hope of further increasing the catalytic activity, mixed-linker MOFs with functional groups in addition to the ionic ingredients (pmtz + -Br – or pmtzm ++ -Br – ) were tested. It has been reported that the amino group can promote the CEC reaction by activating CO 2 . This encouraged us to investigate the mixed-linker MOFs with amino groups. The catalytic activities of these multifunctional MOFs follow a trend similar to that observed for the MOFs without amino groups: MIL-101-NH 2 /pmtzm-TfO (very low conversion) ≪ MIL-101-NH 2 /pmtz-TfO (medium conversion) ≪ MIL-101-NH 2 /pmtz-Br (high conversion) ≪ MIL-101-NH 2 /pmtzm-Br (Table , entries 9–12).…”
Section: Resultsmentioning
confidence: 99%
“…A plausible reaction mechanism based on the experimental results and our previous DFT studies [31,33,37] is proposed, for the cycloaddition of epoxide and CO 2 catalyzed by CPM-200-In/Mg and co-catalyst (Scheme 2). In the first step, Lewis acidic metal centers interact with the O atom of the epoxide ring.…”
Section: Cycloaddition Reaction Mechanismmentioning
confidence: 87%
“…High conversion of propylene oxide (87.3%), epichlorohydrin (90.3%), and allylglycidyl ether (82.1%) might be ascribed from the effective size of the epoxides, facilitating their access to the active sites. Very low conversion (14.3%) was obtained for cyclohexene oxide since the sterically hindered cyclohexene ring may prevent its approach to the Lewis acidic site [32,37,66]. In addition, it is well known that CO 2 -based polycarbonate is easily formed from the reaction of cyclohexene oxide and CO 2 [67].…”
Section: Cycloaddition Of Co 2 With Different Epoxidesmentioning
confidence: 99%
See 1 more Smart Citation